Pengaruh Ekuitas Merek dan Iklan Terhadap Keputusan Pembelian (Studi Kasus Pada Handphone Merek Vivo di Kota Bengkulu) - Deri Peratama; Merta Kusuma (UM. Bengkulu, 2021)
This research aims to; determine the effect of Brand Equity and Advertising on Vivo Smartphone Purchase Decisions in Bengkulu City, to determine the Effect of Brand Equity on Vivo Smartphone Purchase Decisions in Bengkulu City, to determine the Effect of Advertising on Vivo Smartphone Purchase Decisions in Bengkulu City, and to determine the simultaneous influence of Equity Brands and Ads on Vivo Smartphone Purchase Decisions in Bengkulu City. The population of this research is Bengkulu City citizens with a total sample of 60 people. The results of the study show that Brand and Advertising Equity (X) has a positive and significant effect on Purchasing Decisions (Y). This is evidenced by the regression equation of Y = 7.575 + 252 (X1) + 290 (X2), which means that the Brand Equity (X1) variable has a positive effect on purchasing decisions with a value of 0.252. Advertising (X2) also has a positive effect on purchasing decisions with a value of 0.290, with the coefficient of determination of Brand Equity and Advertising variables of 30.1% and the magnitude of the influence of other variables is 69.9%. Based on the results of hypothesis testing with the t test, the Brand Equity variable (X1) gets a value (sig <Î± = 0.035 <0.05) and the t value is 2.160> t table 1.67203. Thus, Ha was accepted and Ho was rejected. This means that Brand Equity has a significant effect on purchasing decisions (Y) and advertising variables (X2) with a value (sig <Î± = 0.021 <0.05) and the tcount value 2.367> t table 1.67203. Then Ha is accepted and Ho is rejected, meaning that advertising has a significant effect on purchasing decisions (Y). While the results of f-test hypothesis testing variable Brand Equity (X1) and Advertising (X2) on purchasing decisions (Y) is (sig <Î± 0.000 <0.05) with Fcount 13,729> Ftable 3.16. Then Ha is accepted and Ho is rejected, meaning that all variables together have a significant effect on purchasing decisions (Y)Â Keywords: Brand Equity, Advertising, Purchase Decision.